Hematuria, an unusual systemic toxicity, in formic acid ingestion: A case report - Satariya Trakulsrichai (2018)
Background: Acid ingestion can cause severe injuries of the upper gastrointestinal tract and the respiratory tract. Besides hydrofluoric acid and selenious acid, systemic toxicities of acid ingestion can occasionally occur. However, hematuria is a rare systemic toxicity reported in caustic poisoning. Objectives: To describe a case of a one-year-old girl who accidentally ingested liquid formic acid. Methods: This patient had severe local corrosive effects including a compromised upper respiratory tract and developed gross hematuria during the hospital admission. Results: Hematuria could be a consequence of acid ingestion. Conclusions: Significant hematuria can be a systemic effect of acid ingestion, but in this case was self-limiting.